Pandangan Tokoh Islam Nahdlatul Ulama (NU) Dan Muhammadiyah Terhadap Wakaf Berjangka - Abd Mubaraq, S.E.,Sy. M.A (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2023)
The research used in this study is explorative qualitative research that aims to reveal the views of Nahdlatul Ulama (NU) and Muhammadiyah figures on waqf futures. The research sample is Nahdlatul Ulama and Muhammadiyah figures. The data collection techniques used are interviews and documentation. The data analysis technique uses coding techniques (open coding, pivoted coding and selected coding). The results of data analysis obtained conclusions on research totaling 10 Islamic figures, 5 people came from Nahdlatul Ulama figures and 5 people came from Muhammadiyah figures, it was found that most of the subjects agreed with the existence of term waqf, by looking at the advantages or benefits possessed from this term waqf greater and many benefits compared to the disadvantages, but with a note that good management must be in accordance with existing laws and regulations and supported by all parties both from the government, waqf institutions, community organizations, community leaders to the wider community. As for the small part of those who disagree with term waqf, it is because in essence the meaning of waqf is to stop, so if the waqf is termed, the meaning of waqf itself will be lost. The next reason is that term waqf has a weakness in intention, meaning that people are still half-hearted about waqf, moreover it is very difficult in terms of administration. Translated with www.DeepL.com/Translator (free version)Keyword: Nahdlatul Ulama (NU), Muhammadiyah, waqf term